Acacia in Sudan - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Sudan is the most important of the gum arabic producing countries, with 80% of the market. The Sudanese farmer grows millet for five years on his field and then plants gum trees. These help to refertilize the land as the gum tree is leguminous and...